The Phyto-phospholipid Complexes- Phytosomes: A Potential Therapeutic Approach for Herbal Hepatoprotective Drug Delivery - Semalty, Ajay; Semalty, Mona; Rawat, M.S.M. (Pharmacognosy Reviews)
A large number of herbal drugs possess the wide spectrum of therapeutic activity. But the potential use of these herbal drugs is limited due to their poor absorption and poor bioavailability after oral administration. The bioavailability can be improved by the use of delivery systems, which can enhance the rate and the extent of drug solubilizing into aqueous intestinal fluids as well as the capacity to cross the lipid rich biomembranes. Phospholipid based drug delivery systems have been found promising for the effective and efficacious herbal drug delivery. Complexing the polyphenolic phytoconstituents in molar ratio with phosphatidylcholine results into a new herbal drug delivery system- "Phytosome". Phytosomes show better pharmacokinetic and therapeutic profile than conventional herbal extracts. This article reviews the current status of phytosomal research and its potential application in hepatoprotective and antihepatotoxic activity.
Keywords: Phytosome; phospholipid complex; herbal drug delivery; phosphatidylcholine